Automation, task content and occupations when skills and tasks are bundled - Sofia Hernnäs (Uppsala University, Department of Economics, 2020)
Automation affects workers because it affects the task content of their occupations. I propose a model which takes two important labor market features into account: (i) automation happens to tasks and (ii) workers with bundled skills work in occupations with bundled tasks. Equilibrium skill returns vary across occupations, and the impact of automation on skill returns is occupation-specific. Using my framework, I find that skill returns in the automated task decline if tasks are gross complements, consistent with much previous literature. Inequality increases in the occupation that is least intensive in the automated task, consistent with the development in Sweden 1985 - 2013. More generally, the model allows exploring how automation of one task affects the task content of occupations, returns to tasks, workers' earnings and inequality.
urn:nbn:se:uu:diva-427080
Keywords: 330; Automatisierte Produktion; Qualifikation; Anforderungsprofil; Lohnniveau; Lohnstruktur; Schweden